PENGATURAN ULANG ZONING RUANG UNTUK MENGETAHUI EFISIENSI BEBAN AC DAN PENCAHAYAAN PADA SUMMARECON OFFICE, JAKARTA - TANTRI OKTAVIA (Serat Rupa: Journal of Design, 2016)
People always work with using energy especially electricity. Global warming gives big impact to electricity consumption. Lighting and air conditioning is important thing to improve a human comfort inside the building. Architecture and interior design give impact to building’s energy consumption. Many high rise rent office are build at the city. High rise office is a branding for the company to look good. Not all building will use for the company, but share with other. The Office design must be good, comfort and good service and cheap for the rent. Energy consumption for operational cost is important thing to decrease rent cost. The solution to make energy efficient is make new design for interior. Air conditioning and lighting is a big part in energy comsumption. Designer must calculate the energy use to decrease an energy comsumption from AC and lighting. This research will collect all heat data from interior and from outdoor penetration. This research use Sun Path Method to know when the buildings have a biggest heat from sunlight everyday. The use of OTTV method (Overall Thermal Tranfer Value) to check a heat value transfer from the façade material. The result will help the designer to make zoning and will make a building efficient Keyword: cooling load; energy efficient; lighting load; rental office; zoning